Construction project management: theory and practice - Jha, Neeraj Kumar (Noida Pearson Education, 2011)
Construction Project Management deals with different facets of construction management emphasizing the basic concepts that any engineering student is supposed to know. The book features computer applications (Primavera and MS Project) used to expla
Keywords: Construction Engineering and Management (ME-CE); Project Management; PROJECT ORGANIZATION; CONSTRUCTION ECONOMICS; CLIENT'S ESTIMATION OF PROJECT COST; CONSTRUCTION CONTRACT